THE EFFECT OF COMPENSATION, EMPLOYEE MOTIVATION, AND CHANGE MANAGEMENT ON EMPLOYEE PERFORMANCE AT PAM TIRTA MANGKALUKU PALOPO CITY - Amalia Amalia; Edi Maszudi; Adil Adil (Universitas Nusa Cendana, 2025)
This research investigates how compensation, employee motivation, and change management impact employee performance at PAM Tirta Mangkaluku in Palopo City. The research utilizes a quantitative approach. The techniques for gathering data include both primary and secondary sources. Primary data was collected by issuing questionnaires to participants. The sample for this study consisted of 35 employees from PAM Tirta Mangkaluku in Palopo City. The analysis employed was statistical, using SPSS 22 for tools such as the validity test, reliability test, T test, and F test. Findings from this study reveal that (1) Compensation positively and significantly influences employee performance, (2) Employee motivation significantly and positively affects employee performance, (3) Change management also has a significant and positive impact on employee performance, and (4) When considered together, Compensation, Employee Motivation, and Change Management have a significant and positive effect on Employee Performance. Keywords: Compensation; Employee Motivation; Change Management; Employee Performance